Prevalence of Pediculosis Capitis in Indonesia - Reqgi First Trasia (Insights in Public Health Journal, 2022)
Head lice infestation is still a health problem in Indonesia. Currently, there has been a lot of research on the incidence of pediculosis capitis. However, there are still few articles that systematically review the incidence of head lice infestation. The purpose of writing this article is to examine cases of pediculosis capitis in several regions in Indonesia in order to obtain systematic and comprehensive prevalence data. A literature search was carried out in October 2021 through Google Scholar and obtained 13 relevant articles. Based on the above review, it can be concluded that the highest incidence of pediculosis capitis is in Islamic boarding schools, attacking elementary school-aged children, with a prevalence range of 29.3%-88.9% and can occur throughout Indonesia. This condition can be caused by a lack of personal hygiene, so that it can continue to be a source of infestation for children around it.